STRATEGI KOLABORATIF KEPALA SEKOLAH DAN GURU DALAM MENCIPTAKAN LINGKUNGAN SEKOLAH BEBAS BULLYING DI SEKOLAH DASAR - Hegel Bintang Raihan; I Made Ratih Rosanawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of bullying, the collaborative strategies between the principal and teachers, and the challenges in creating a bullying-free school environment at the elementary school level. This research employed a qualitative approach with a descriptive design. The subjects of the study consisted of the principal, a fifth-grade teacher, and two students involved in bullying cases (a victim and a perpetrator). Data were collected through observation, semi-structured interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, with data validity ensured through triangulation techniques. The results showed that bullying was predominantly in the form of verbal and social bullying, such as teasing, name-calling, excessive joking, and social exclusion, as well as minor physical actions in some cases. The collaborative strategies were carried out through preventive and curative approaches. Preventive efforts included character education, classroom agreements, socialization of the impacts of bullying, and regular evaluation between the principal and teachers. Curative efforts involved dialogical approaches, guidance for perpetrators, emotional support for victims, and mediation. The challenges faced included victims’ reluctance to report incidents, a culture of teasing considered as jokes, and limited time for teachers to provide assistance.